Synergism between rhizobium strains and soil bioactivator favor sustainable production of Arachis pintoi - de Oliveira, Tayla Évellin; Aparecida Tomaz do Prado, Raphaela; Vilela de Rezende, Adauton; Aparecida Florentino, Ligiane (Revista Ceres, 2023)
The objective of this study was to evaluate the influence of a commercial product, a soil bioactivator, on the establishment and efficiency of symbiosis between rhizobia and Arachis pintoi (forage peanut). The experiment was conducted in a greenhouse in 8 dm3 pots and 12 treatments were used, ten inoculated with different strains of rhizobia and two without inoculation (presence or absence of mineral nitrogen), associated or not with the application of soil bioactivator. The experimental design used was a randomized block design with four repetitions. The experiment was conducted until the time of flowering, when the agronomic characteristics referring to the shoot dry matter (SDM) and root (RDM), relative symbiotic efficiency (RS), number (NN) and nodule dry matter (NMS) and the bromatological characteristics, given by the content of crude protein (CP), neutral detergent fiber (NDF) and acid (ADF) were evaluated. The use of soil bioactivator did not influence the bromatological characteristics, but potentiated the inoculation with rhizobia strains, UNIFENAS 03-16, UNIFENAS 03-31 and UNIFENAS 03-36, effectively contributing to increases in the values of SDM, RS and NN, thus constituting a sustainable alternative for the production of A. pintoi.